Using VAR to Determine the Value of a Company - Bozsik, Sándor; Szemán, Judit (Theory, Methodology, Practice – Review of Business and Management, 2005)
This paper deals with one particular basic problem of discounted cash flow methods, and one of their possible solutions. the most accepted company evaluation method determines the market value of an enterprise to estimate the incremental cash flows from the operation (free cash flow), then to discount them with the weighted average cost of capital (WACC), which fits to the risk of the company operation. The problem occurs, when we should like to determine the weights for WACC calculation, because theoretically these weights are the market value of capital elements – among them the market value of equity, so we should know the result before the calculation. This dilemma cannot be solved in the frame of discounted cash flow methods, therefore alternative company methods – first of all – the option pricing model – emerged. However the application of option pricing models come together also with serious problems, that’s why the authors offer another methods to solve the dilemma – the application of VAR methods. This method is presented by the case of Elmü Rt – which is the largest electricity utility in Hungary.